2021
DOI: 10.1029/2020ja028893
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Calculate the Fluxgate Magnetometer Offset in the Interplanetary Magnetic Field: 1. Using Alfvén Waves

Abstract: We propose a new method to calculate the fluxgate magnetometer offset in the interplanetary magnetic field • This method is based on the highly Alfvénic property of the interplanetary magnetic field • This method is able to get a zero offset with a high accuracy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 34 publications
(61 reference statements)
0
36
0
Order By: Relevance
“…Alfvén waves do not change the magnetic field strength (Keiling, 2008 Wang and Pan (2021) found that there exists an OOL with good linearity in the offset cube, and this line passes through the real zero offset.…”
Section: Wang-pan Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…Alfvén waves do not change the magnetic field strength (Keiling, 2008 Wang and Pan (2021) found that there exists an OOL with good linearity in the offset cube, and this line passes through the real zero offset.…”
Section: Wang-pan Methodsmentioning
confidence: 95%
“…Recently, a new method has been proposed by Wang and Pan (2021) to calculate the zero offset of the FGM based on properties of the Alfvén wave. For the convenience of description, we refer to this new method as the Wang-Pan method.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations